2012
DOI: 10.1128/mbio.00035-12
|View full text |Cite
|
Sign up to set email alerts
|

Nontypeable Pneumococci Can Be Divided into Multiple cps Types, Including One Type Expressing the Novel Gene pspK

Abstract: ABSTRACTAlthough virulence ofStreptococcus pneumoniaeis associated with its capsule, some pathogenicS. pneumoniaeisolates lack capsules and are serologically nontypeable (NT). We obtained 64 isolates that were identified as NT “pneumococci” (i.e., bacteria satisfying the conventional definition but without the multilocus sequence typing [ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
170
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(171 citation statements)
references
References 55 publications
1
170
0
Order By: Relevance
“…Genetic studies of cps loci from NT isolates revealed two broad NT groups (110,111). Group I NT isolates retain the characteristic genetic elements of the cps locus (112,113), while cps loci of group II NT isolates do not encode PS synthesis machinery but have genes for distinct proteins such as PspK (also identified as NspA) (100,111) and homologs of the putative peptide permease AliB (110,111). These proteins may facilitate epithelial adhesion and colonization, as almost all NT isolates from the NP belong to group II.…”
Section: Nontypeable Pneumococcimentioning
confidence: 99%
“…Genetic studies of cps loci from NT isolates revealed two broad NT groups (110,111). Group I NT isolates retain the characteristic genetic elements of the cps locus (112,113), while cps loci of group II NT isolates do not encode PS synthesis machinery but have genes for distinct proteins such as PspK (also identified as NspA) (100,111) and homologs of the putative peptide permease AliB (110,111). These proteins may facilitate epithelial adhesion and colonization, as almost all NT isolates from the NP belong to group II.…”
Section: Nontypeable Pneumococcimentioning
confidence: 99%
“…Firstly, there has been an increase in NESp prevalence as it was observed that strains increased from 1.5% in 2001 to 5.1% in 2006. 32 However, at any point in time NESp frequency can be between 3–19% worldwide. 33 This is important, as current conjugate vaccines do not protect against NESp.…”
Section: Discussionmentioning
confidence: 99%
“…These strains have been associated with causing conjunctivitis, IPD, otitis media, and carriage. 32 Strains can be divided into two classes. Class I types contain the cps locus which normally codes for the CPS; however, mutations or disruptions prevent the bacteria from making a capsule.…”
Section: Characteristics Of the Bacteriummentioning
confidence: 99%
See 1 more Smart Citation
“…Group I NT strains possess a cps locus very similar to that of encapsulated strains. Group II NT strains lack the vast majority of the cps locus and instead harbor other genes, such as pspK (encoding an LPXTG-anchored protein potentially involved in epithelial adhesion and invasion), nspA [encoding a novel surface protein which may interact with the human poly(Ig) receptor], and genes with significant sequence similarity to aliB, which encodes a pep-tide-binding molecule associated with an ABC transporter (19)(20)(21)(22)(23). While it is clear that the replacement of the entire cps locus results in an acapsular strain, the molecular mechanism(s) responsible for reduced/loss of capsule in conjunctival clinical isolates with a seemingly intact cps locus is incompletely understood.…”
mentioning
confidence: 99%